Upregulation of Chemoresistance by Mg2+ Deficiency through Elevation of ATP Binding Cassette Subfamily B Member 1 Expression in Human Lung Adenocarcinoma A549 Cells - Saki Onuma; Aya Manabe; Yuta Yoshino; Toshiyuki Matsunaga; Tomohiro Asai; Akira Ikari (Cells, 2021)
Several anticancer drugs including cisplatin (CDDP) induce hypomagnesemia. However, it remains fully uncertain whether Mg2+ deficiency affects chemosensitivity of cancer cells. Here, we investigated the effect of low Mg2+ concentration (LM) on proliferation and chemosensitivity using human lung adenocarcinoma A549 cells. Cell proliferation was reduced by continuous culture with LM accompanied with the elevation of G1 phase proportion. The amounts of reactive oxygen species (ROS) and stress makers such as phosphorylated-ataxia telangiectasia mutated and phosphorylated-p53 were increased by LM. Cell injury was dose-dependently increased by anticancer drugs such as CDDP and doxorubicin (DXR), which were suppressed by LM. Similar results were obtained by roscovitine, a cell cycle inhibitor. These results suggest that LM induces chemoresistance mediated by ROS production and G1 arrest. The mRNA and protein levels of ATP binding cassette subfamily B member 1 (ABCB1) were increased by LM and roscovitine. The LM-induced elevation of ABCB1 and nuclear p38 expression was suppressed by SB203580, a p38 MAPK inhibitor. PSC833, an ABCB1 inhibitor, and SB203580 rescued the sensitivity to anticancer drugs. In addition, cancer stemness properties were suppressed by SB203580. We suggest that Mg2+ deficiency reduces the chemotherapy sensitivity of A549 cells, although it suppresses cell proliferation.